Women of a promiscuous nature [large type] - Everhart, Donna (Center Point Large Print, 2026)
"On a brisk February morning while walking to the diner where she works, twenty-four-year-old Ruth Foster is stopped by the local sheriff. He insists she accompany him to a health clinic, threatening to arrest her if she doesn't undergo testing in order to preserve decency and prevent the spread of sexual disease. Though Ruth has never shared more than a chaste kiss with a man, she is detained at the State Industrial Farm Colony for Women. Some women are there because they were reported for promiscuity by neighbors, husbands, strangers. Some were accused of prostitution. Others were just pretty and unmarried. Or poor and "suspicious." One was eating dinner alone in a restaurant. Another spoke to a soldier. Superintendent Dorothy Baker, convinced that she's transforming degenerate souls into upstanding members of society, oversees the women's medical treatment and "training" until they're deemed ready for parole. Sooner or later, everyone at the Colony learns to abide by Mrs. Baker's rule book or face the consequences--solitary confinement, grueling work assignments, and worse."--